The epidemiology of assault across the West Midlands. Issue 5 (3rd September 2003) - Downing, A; Cotterill, S; Wilson, R
Abstract : Objectives: The purpose of this study is to look at accident and emergency (A&E) attendances and admissions after assault in the West Midlands NHS region across a wide range of acute units. Methods: This study used data from two sources, the A&E Minimum Data Set and the Hospital Episode Statistics database. Analyses were based on data from 12 of the 21 acute trusts in the West Midlands NHS region for the period 1 April 1999 to 31 March 2000. Results: Analyses were performed on 15 969 A&E attendances and 1596 admissions. Some 67.4% of attenders and 84.2% of those admitted were male. The mean age of the patients was between 27 and 29 years. Attendance peaked between 2100 and 0259, especially on Friday and Saturday night. The most common injury was to the head. Some 75.3% of A&E attenders were discharged home. The average stay in hospital was two days and six deaths were recorded. Those living in the most deprived areas were nearly four times more likely to be admitted than those in the least deprived areas (175.9 per 1000 compared with 45.1 per 1000). Conclusions: This study shows assault is predominately a male phenomenon, worst in the evenings and at weekends, and is positively related to deprivation. It is probable that the levels recorded will be an underestimate, however with some additions to the information collected hospital records could create the basis for a comprehensive surveillance system.